FROM THE EDITORS - Salameh, Franck (The Levantine Review, 2012)
A peer-reviewed electronic journal, The Levantine Review publishes scholarship (in English, French, Arabic, Hebrew, Turkish, Syriac, and Levantine vernaculars) on the history, cultures, religions, politics, and the intellectual, philological, and literary traditions of the contemporary Levant and Near East.